Malpraktik dalam Abortus Provocatus di Kota Makassar: Kajian Sadd al-Dzari'ah Sebagai Tindakan Preventif Kejahatan Medis - Fatra, Meyhira Fatrizia; Hasan, Hamzah; Fatmawati, Fatmawati (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This study aims to analyze the forms of malpractice in illegal abortion provocatus in Makassar City, evaluate the legal aspects of the perpetrators, and examine the practice through the sadd al-dzari'ah approach in Islamic law as a preventive strategy against medical crimes. The practice of abortion performed without professional medical supervision, especially by non-medical individuals such as birth attendants or untrained personnel, poses a serious threat to the safety of women's lives and reproductive health. This research uses a qualitative approach with a type of field research. Data collection techniques are carried out through observation, in-depth interviews, and documentation studies, which are then analyzed descriptive-qualitatively. Field findings show that illegal abortions in Makassar are often performed without proper medical standards, causing harmful physical and psychological complications. Several cases have been handled by law enforcement officials and resulted in criminal verdicts against the perpetrators. From the perspective of sadd al-dzari'ah, this practice is considered to pave the way for wider damage (mafsadah), as it ignores the protection of the soul and violates the basic principles of Islamic law. This study recommends strengthening the legal system and health policies oriented towards prevention, as well as the need for public education based on Islamic values to close the gap in the occurrence of illegal abortion practices and increase awareness of the importance of reproductive health protection.